Minutes of the CCAFS 7th Independent Steering Committee Meeting, 12 May 2020 - CGIAR Research Program on Climate Change, Agriculture and Food Security (2020)
In May 2020 the CGIAR Research Program on Climate Change, Agriculture and Food Security (CCAFS) held its 7th virtual Independent Steering Committee meeting.